RABIES EPISODE AND CONTROL MEASURES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article describes the diagnostic examination of animal heads brought for examination with suspicion of rabies at the Virology Laboratory of the Samarkand Regional State Center for the Prevention and Control of Rabies, and the fact that dogs are the main cause of the spread of these diseases.